An exploration of the role of pharmacists within general practice clinics: the protocol for the pharmacists in practice study (PIPS) - Tan Edwin; Stewart Kay; Elliott Rohan A; George Johnson (BMC, 2012)
Abstract Background Medication-related problems are a serious concern in Australian primary care. Pharmacist interventions have been shown to be effective in identifying and resolving these problems. Collaborative general practitioner-pharmacist services currently available in Australia are limited and underused. Limitations include geographical isolation of pharmacists and lack of communication and access to patient information. Co-location of pharmacists within the general practice clinics is a possible solution. There have been no studies in the Australian setting exploring the role of pharmacists within general practice clinics. The aim of this study is to develop and test a multifaceted practice pharmacist role in primary care practices to improve the quality use of medicines by patients and clinic staff. Methods/design This is a multi-centre, prospective intervention study with a pre-post design and a qualitative component. A practice pharmacist will be located in each of two clinics and provide short and long patient consultations, drug information services and quality assurance activities. Patients receiving long consultation with a pharmacist will be followed up at 3 and 6 months. Based on sample size calculations, at least 50 patients will be recruited for long patient consultations across both sites. Outcome measures include the number, type and severity of medication-related problems identified and resolved; medication adherence; and patient satisfaction. Brief structured interviews will be conducted with patients participating in the study to evaluate their experiences with the service. Staff collaboration and satisfaction with the service will be assessed. Discussion This intervention has the potential to optimise medication use in primary care clinics leading to better health outcomes. This study will provide data about the effectiveness of the proposed model for pharmacist involvement in Australian general practice clinics, that will be useful to guide further research and development in this area. Trial registration Australian New Zealand Clinical Trials Registry: ACTRN12612000742875